1998
DOI: 10.1111/j.1600-051x.1998.tb02407.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo Study of the chlorhexidine release profile of the PerioChipTM in the gingival crevicular fluid, plasma and urine

Abstract: The release profile of chlorhexidine from the PerioChip (Chip), a biodegradable local delivery system that contains 2.5 mg of chlorhexidine gluconate (CHX) in a cross-linked hydrolyzed gelatin matrix, into the gingival crevice, was evaluated in an in vivo, open label, single-center, 10-day pharmacokinetic study conducted on 19 volunteers with chronic adult periodontitis. Each volunteer had a single chip inserted into each of 4 selected pockets, with probing pocket depths of between 5-8 mm, at time 0. Gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 19 publications
7
48
0
3
Order By: Relevance
“…Our results are similar to those reported in earlier multicentre clinical trials by Killoy [14], Soskolne et al [15], Jeffcoat et al [16] and Paolantonio et al [17], where CHX applied as a local drug delivery significantly reduced plaque index scores, bleeding on probing, probing pocket depth and gain in CAL< although no differences in gingival inflammation scores between the test and control sites were found at baseline. GI scores were reduced significantly in the test and control sites from baseline till the end of 3 months, which was in accordance with the findings observed by Soskolne et al [15], Jeffcoat et al [16] and Heasman et al [18].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are similar to those reported in earlier multicentre clinical trials by Killoy [14], Soskolne et al [15], Jeffcoat et al [16] and Paolantonio et al [17], where CHX applied as a local drug delivery significantly reduced plaque index scores, bleeding on probing, probing pocket depth and gain in CAL< although no differences in gingival inflammation scores between the test and control sites were found at baseline. GI scores were reduced significantly in the test and control sites from baseline till the end of 3 months, which was in accordance with the findings observed by Soskolne et al [15], Jeffcoat et al [16] and Heasman et al [18].…”
Section: Discussionsupporting
confidence: 94%
“…GI scores were reduced significantly in the test and control sites from baseline till the end of 3 months, which was in accordance with the findings observed by Soskolne et al [15], Jeffcoat et al [16] and Heasman et al [18]. This reduction may be attributed to SRP, patient education and motivation.…”
Section: Discussionsupporting
confidence: 90%
“…Its safety and efficacy in reducing probing depth and bleeding on probing has been tested in clinical trials [19][20][21][22]. An in vitro release profile of chlorhexidine of 1105µg at 24 hours to 40µg by 7 days has been noted which is however not similar to the release profile of Periochip [19,38]. Periochip is a controlled local delivery system containing 2.5 mg of chlorhexidine gluconate incorporated into a biodegradable chip of hydrolyzed bovine gelatine has proven to inhibit more than 99% of subgingival microorganisms from periodontal pockets.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration exceeds the minimum inhibitory concentration for more than 99% of subgingival microorganisms. In Periochip [38] an initial peak concentration of CHX in the GCF at 2 h post-Chip insertion (2007 µg/ml) was seen with slightly lower concentrations between 1300-1900 µg/ml being maintained over the next 96 h. The CHX concentration then progressively decreased until 9 th day with significant CHX concentrations (mean=57 µg/ml) still being detectable at 9 th day [38]. However, the results of this are in contradiction to those of Medaiah S et al, [39] study that showed no improvement with the adjunctive use of CHX chip.No adverse clinical events occurred in any of the study patients after placement of the collagen-based chlorhexidine chip.…”
Section: Discussionmentioning
confidence: 99%
“…Untersuchungen an verschiedenen Schleimhäuten zeigten, dass keine relevante systemische Resorption von Chlorhexidin stattfindet (bei bukkaler, vaginaler Anwendung) [8,9,10]. Entsprechende Untersuchungen beim intermittierenden Katheterismus gibt es nicht.…”
Section: Resorption Von Chlorhexidinunclassified